Estimaciones del PIB mensual basadas en el IGAE - Rocio Elizondo (Banco de México, 2012)
– This article presents three methods to estimate the logarithm of monthly real GDP in Mexico from the Global Indicator of Economic Activity (IGAE): (1) a deterministic approach using the IGAE growth rate; (2) an extension of Denton method; and, (3) the Kalman filter. In these methods the monthly GDP is regarded as an unobservable variable that is approximated using only the IGAE. Results suggest that the method based on the Kalman filter seems to fit better the observed data of quarterly GDP under several error measures. By analyzing different estimation periods it was found that the parameters corresponding to the filter remained relatively stable over the period of study. Therefore, this method was used to perform out-of-sample forecasts.
Keywords: C22; D24; E23; E27; 330; Gross Domestic Product; Global Indicator of Economic Activity; Kalman Filter; Denton Method; Forecasts; Sozialprodukt; Wirtschaftsindikator; Zustandsraummodell; Mexiko